TINGKAT KEBERDAYAAN PETANI PADI SAWAH BERDASARKAN KARAKTERISTIK SOSIAL EKONOMI - Zuriani, Zuriani; Martina, Martina; Adhiana, Adhiana; Riani, Riani (LPPM Universitas Malikussaleh - Indonesia, 2024)
Lowland rice farmers in North Aceh Regency do not yet have a good level of ability in developing rice agribusiness. Ability is one element of empowerment. Low ability shows low empowerment. Empowered farmers mean having adequate knowledge, attitudes and skills so they are able to manage their farming business well. The research aims to determine the level of empowerment of rice farmers based on socio-economic characteristics. This research uses primary data derived from interviews with lowland rice farmers. Data analysis uses qualitative descriptive methods. The results of the analysis show that there are differences in levels of empowerment when viewed based on age, income and land area. Meanwhile, in terms of education, experience, number of dependents and source of income, it is generally known that all farmers are in the same category, namely empowered.